Facing the Multicore-Challenge III Aspects of New Paradigms and Technologies in Parallel Computing - Keller, Rainer; Kramer, David; Weiss, Jan-Philipp.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This state-of-the-art survey features topics related to the impact of multicore, manycore, and coprocessor technologies in science and large-scale applications in an interdisciplinary environment. The papers included in this survey cover research in mathematical modeling, design of parallel algorithms, aspects of microprocessor architecture, parallel programming languages, hardware-aware computing, heterogeneous platforms, manycore technologies, performance tuning, and requirements for large-scale applications. The contributions presented in this volume are an outcome of an inspiring conference conceived and organized by the editors at the University of Applied Sciences (HfT) in Stuttgart, Germany, in September 2012. The 10 revised full papers selected from 21 submissions are presented together with the twelve poster abstracts and focus on combination of new aspects of microprocessor technologies, parallel applications, numerical simulation, and software development; thus they clearly show the potential of emerging technologies in the area of multicore and manycore processors that are paving the way towards personal supercomputing and very likely towards exascale computing.
Keywords: Computer science; Memory management (Computer science).; Computer system performance; Software engineering; Computer graphics; Computer Science; Processor Architectures; System Performance and Evaluation; Software Engineering/Programming and Operating Systems; Computer Graphics; Arithmetic and Logic Structures; Memory Structures